2014
DOI: 10.1111/1467-8489.12071
|View full text |Cite
|
Sign up to set email alerts
|

Nonmarket valuation in developing countries: incorporating labour contributions in environmental benefits estimates

Abstract: There are limitations associated with the application of nonmarket valuation techniques, including choice experiments, in subsistence economies. In part, this is due to the concern that using money as a mode of contribution may not capture the potential contribution of low-income households. To address this limitation, respondents in this study were provided with the option of contributing towards the management of invasive plants in labour terms if they were unwilling to contribute in monetary terms. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
(53 reference statements)
1
31
0
Order By: Relevance
“…We found that higher positive preference and MWTP on the land use program are affected by higher income, having a farm and community organization membership. Similarly, a previous study focusing on residents of the buffer zone of Chitwan National Park in Nepal and selected vehicle payment (annual membership fee or labor contribution) showed that the average household WTP of the monetary group is consistently higher than that of their neighbors who prefer to contribute labor [36]. A detailed and comprehensive analysis reveals the local residents' various preferences towards land-use management strategies for community conservation in a forest park.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…We found that higher positive preference and MWTP on the land use program are affected by higher income, having a farm and community organization membership. Similarly, a previous study focusing on residents of the buffer zone of Chitwan National Park in Nepal and selected vehicle payment (annual membership fee or labor contribution) showed that the average household WTP of the monetary group is consistently higher than that of their neighbors who prefer to contribute labor [36]. A detailed and comprehensive analysis reveals the local residents' various preferences towards land-use management strategies for community conservation in a forest park.…”
Section: Discussionmentioning
confidence: 79%
“…Table 5 depicts the results of the LCM analysis with two latent groups. It found out that the respondents' income [6,36,53], duration of residence, membership in the community group [6], land ownership [53,54] and occupation were significant [55]. The group membership characteristic included farmers and non-farmers.…”
Section: Heterogeneity Test Of the Lcm Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a related study Rai and Scarborough (2014) report the findings of a similar DCE, however, on this occasion a split sample approach was used where the respondent was permitted to choose their preferred payment option, either money or labour, for the DCE. Roughly 35 % chose the money option whilst the remainder (65 %) chose the labour option.…”
Section: Dce Studiesmentioning
confidence: 99%